Elevating the potential of CAR-T cell therapy in solid tumors: exploiting biomaterials-based delivery techniques - Tang, Yuxiang; Yang, Xiaoyu; Hu, Hang; Jiang, Huiwen; Xiong, Wei; Mei, Heng; Hu, Yu (Frontiers in Bioengineering and Biotechnology, 2024)
Chimeric antigen receptor (CAR) T cells exhibit promising progress in addressing hematologic malignancies. However, CAR-T therapy for solid tumors remains limited, with no FDA-approved CAR-T products available for clinical use at present. Primary reasons include insufficient infiltration, accumulation, tumor immunosuppression of the microenvironment, and related side effects. Single utilization of CAR-T cannot effectively overcome these unfavorable obstacles. A probable effective pathway to achieve a better CAR-T therapy effect would be to combine the benefits of biomaterials-based technology. In this paper, comprehensive biomaterials strategies to break through these obstacles of CAR-T cell therapy at the tumor sites are summarized, encompassing the following aspects: 1) generating orthotopic CAR-T cells; 2) facilitating CAR-T cells trafficking; 3) stimulating CAR-T cells expansion and infiltration; 4) improving CAR-T cells activity and persistence; 5) reprogramming the immunosuppressive microenvironments. Additionally, future requirements for the development of this field, with a specific emphasis on promoting innovation and facilitating clinical translation, are thoroughly discussed.